PENYELESAIAN SENGKETA PERCERAIAN DALAM ADAT BATAK TOBA “DALIHAN NATOLU” DI KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Anggita Yekholia Berti; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The provisions on customary justice are not included in the legislation, but the facts still apply in the community, especially in rural and provinces outside of Java island. In the Toba Batak indigenous people who are mostly Christians, are not allowed to divorce if not for death. Therefore there is a familial system in the custom of Batak Toba Dalihan Natolu who serves as a mediator in the settlement of dispute divorce indigenous Batak Toba. Dalihan Natolu consists of Hula-Hula, Boru, Dongan Tubu from each side of the dispute. Lately Toba Batak indigenous people tend to choose to resolve their divorce dispute through the litigation path rather than customary dispute settlement through Dalihan Natolu.This study uses a kind of sociological juridical research that sees the correlation between law and society. This research was conducted in Tanjung Morawa Subdistrict of Deli Serdang Regency, while the population and sample were all related parties in the problem to be studied. Sources of data used, primary data, secondary data, and tertiary data, data collection techniques in this study with interviews, and literature review.From the results of research there are two main things that can be concluded. First, the role of Dalihan Natolu as a mediator in the settlement of Toba Batak customary divorce problem is Dalihan Natolu has the role of giving advice and suggestions, to be a mediator in the problems that occur between the parties who want to divorce without taking side to either party and the decision remains in return to both parties. Dalihan Natolu seeks to reunite the two sides, because since long ago in the Toba Batak adat strongly opposed to the divorce. Secondly, the efforts to make Dalihan Natolu more leverage in the settlement of dispute disputes in the future in Tanjung Morawa Sub-district Deli Serdang District is the introduction made by traditional leaders or chairman of clan association (parsahutaon) including the parents, the introduction of the norm -normal arranged in Dalihan Natolu to the young generation. Then encourage the members of the punguan (community) to further empower the Dalihan Natolu tool as the first alternative in settling disputes between them before bringing the matter to court. The next role of the government to encourage people to resolve disputes by using customary institutions Dalihan Natolu by socializing Perda No.10 of 1999 on Customary Institution Dalihan Natolu as a customary discussion Batak in the form based on mutual cooperation and kinship.Keyword: Dispute-Divorce Settlement-Dalihan Natolu Dispute